Improving Science Literacy Skills Through the Experimental Method of Playing with Soap Bubbles in Early Childhood - Aunillah, Asqi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The research is motivated by increasing scientific literacy through experimental methods. Literacy is not only limited to discussing the ability to write and read, but can expand understanding which can improve critical thinking skills, problem solving in a different context, effective communication, potential development, and active in society (Eliza, 2022). Therefore, scientific literacy needs to be introduced from an early age because it is important to train the development of scientific concepts and behavior. This article discusses improving scientific literacy skills through the experimental method of playing with soap bubbles in early childhood. The research method used is the observation method, this research was carried out not only by researchers but also with educators. The aim of this research is to determine the development of scientific literacy in early childhood and also children's enthusiasm for experimenting.